Financial Instruments to Hedge Commodity Price Risk for Developing Countries - Lu, Yinqiu (IMF Working Papers; Working Paper, 2008)
Many developing economies are heavily exposed to commodity markets, leaving them vulnerable to the vagaries of international commodity prices. This paper examines the use of commodity options-including plain vanilla, risk reversal, and barrier options-to hedge such risk. It then proposes the use of a new structured product-a sovereign Eurobond with an embedded option on a specific commodity price. By extracting commodity price risk out of the bond, such an instrument insulates the bond default risk from commodity price movements, allowing it to be marketed at a lower credit spread. The product is also designed to help developing countries establish a credit derivatives market, which would in turn enhance the marketability and liquidity of sovereign bonds.